Arendt and Technology: Prophecy of an endless posthumanism - García Labrador, Julián (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This paper presents Arendt's posthumanist prophecies and establishes the relationship with her analysis of modern technoscience. It stresses the ambivalent role that technology plays in her thought. Arendt affirms, on the one hand, the political neutrality of technology; but, on the other hand, she foresees that the future modification of the human condition, thanks to technology, could lead to a stage of such passivity that humanity abandons itself to an endless vital process in which a properly human world is no longer possible.